Islamic Crowdfunding And Sustainable Msme Management In Indonesia: The Effects Of Organisational Orientation Rhetoric, Fund Effectiveness, And Financial Capability On Crowdfunding Success And Performance - Susiang , Maria Imelda Novita (Novatio : Journal of Management Technology and Innovation, 2024)
This study delves into Sharia-compliant crowdfunding's dynamics and its impact on the long-term sustainability of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia. It investigates how factors like fund efficacy, financial capabilities, and organizational orientation rhetoric influence crowdfunding success and subsequent business performance. Utilizing Structural Equation Modeling (SEM) with Partial Least Squares (PLS), data from MSME owners, managers, and crowdfunding platform administrators is analyzed. The findings reveal significant positive correlations between organizational orientation rhetoric, fund efficacy, financial capability, crowdfunding success, and business performance. Key contributors to crowdfunding success include financial capacity, fund efficacy, and organizational orientation rhetoric, all of which also positively influence business performance. Mediation analysis further illustrates how crowdfunding success mediates the relationships between organizational orientation rhetoric, fund effectiveness, financial capabilities, and business performance. This study underscores the advantages of Sharia-compliant crowdfunding for Indonesian MSMEs, such as improved access to capital, enhanced business performance, strategic organizational focus, effective crowdfunding platforms, supportive policies, and increased investor trust fostered by transparency and accountability.